MANAJEMEN PIMPINAN PESANTREN DALAM MENINGKATKAN KUALITAS PROGRAM TAHFIDZ AL QUR’AN DI PONDOK PESANTREN NURUL IMAN KOTA JAMBI - Zuyun Siti Nurfina Susanti; Raudhatul Jannah; Ahmad fikri (Jurnal Manajemen Pendidikan, 2026)
This study aims to understand and describe how the leadership management of Nurul Iman Islamic Boarding School improves the quality of the Tahfidz Al-Qur’an program. Specifically, this research focuses on: (a) describing the management implemented by the pesantren leadership in enhancing the quality of the Tahfidz Al-Qur’an program, (b) identifying the obstacles faced in its implementation, and (c) determining the solutions carried out by the leadership to overcome these challenges.This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The subjects of this study include the pesantren leader, the Tahfidz program manager, and the Tahfidz teachers at Nurul Iman Islamic Boarding School, Ulu Gedong Village, Danau Teluk District, Jambi City. The findings show that the pesantren leadership implements the management of the tahfidz program through regular motivation for students, adjusting the tahfidz schedule to avoid conflicts with formal learning activities, adding more instructors, and conducting periodic evaluations. The challenges encountered include the limited number of tahfidz teachers, low motivation among some students, inadequate facilities such as suitable tahfidz rooms and audio equipment, as well as limited study time since students must divide their schedules between general subjects and pesantren activities.